Antibacterial and anti-biofilm activities of Disaspidin BB against Staphylococcus epidermidis - Lan, Shihua; Chen, Xiaofeng; Yin, Chuanping; Xie, Shengjun; Wang, Shuaishuai; Deng, Rongrong; Shen, Zhibin (Frontiers in Microbiology, 2023)
Introduction Staphylococcus epidermidis infections are an important concern in worldwide, especially when associated with biofilms, and resistance of this agent to many drugs makes the situation even worse. We investigated the inhibitory effect of Disaspidin BB obtained from plant extracts and purifications on clinical S. epidermidis strains and their biofilms, and preliminarily investigated its mechanism of of its anti-biofilm activity. Methods and Results The broth dilution method was used to determine the minimum inhibitory concentrations (MIC) of Disaspidin BB on 11 clinical S. epidermidis strains (MIC value of 0.63 2.5 μg/ml). SEP-05 was found to be erythromycin-resistant (MIC value>8 μg/ml) and Disaspidin BB sensitive with an MIC value of 0.63 μg/ml. The time-kill curve assay indicated that the antibacterial activity of Disaspidin BB against SEP-05 with concentration dependence. The metabolic activity and total biomass of the drug-treated SEP-05 biofilm in each stage were significantly inhibited by the crystalline violet and XTT assay, and the scavenging effect of Disaspidin BB on SEP-05 biofilm was also confirmed by SEM observation. The results of real-time quantitative PCR showed that subinhibitory concentrations Disaspidin BB can inhibit biofilm formation by affecting the expression level of key genes (aap, atlE, icaA, luxS, recA) in SEP-05 biofilm formation. In addition, the content of polysaccharides, proteins and extracellular DNA in biofilm matrix after the intervention of Disaspidin BB was significantly reduced, and it was tentatively determined that the ability of SEP-05 biofilm formation and its stability were thus disturbed. Discussion The results show that Disaspidin BB has promising antibacterial effect on erythromycin-resistant S. epidermidis and significant scavenging effect on its biofilm, which provides a theoretical basis for the further development of BB as a new drug for the treatment of skin infections caused by S. epidermidis.